Невтомний дослідник та захисник природи - Baransky, O.R.; Moroz, P.A. (M.M. Gryshko National Botanical Garden of the NAS of Ukraine, 2010)
Becoming Victor Ivanovich Melnik as famous botany is clarified; contribution of the scientist on development of plant geography, phytosozology and introduction of rare species of natural flora is opened. It is marked Victor Ivanovich’s role as founder of school of phytosozology in Ukraine. His most important scientific works are represented.